Prevention and Management of Post-ERCP Pancreatitis - Sahakian, Ara B; Buxbaum, James L; Van Dam, Jacques (JOP. Journal of the Pancreas, 2014)
Pancreatitis remains as one of the most frequent and serious complications of ERCP. Research has identified several patient-related and procedural risk factors, which help guide the endoscopist in prophylaxis and management of pancreatitis. Recent studies have had a major impact on both procedural techniques and pharmacological methods for prophylaxis of post-ERCP pancreatitis. The purpose of this article is to review the relevant literature and describe the most recent and effective approaches in prevention and management of post-ERCP pancreatitis. Image: Pancreas stenting.